Carbon Monoxide Poisoning Cases Autopsied in South Marmara Region - Eren, Filiz; Gürses, Murat Serdar; Ural, Mustafa Numan; İnanır, Nursel Türkmen and Eren, Bülent and Vojtisek, Tomas (The Bulletin of Legal Medicine, 2014)
Carbonmonoxide (CO) related deaths, which are generally preventable accidents that include accidents due to the coal stoves and water heaters in bath at home, the mining accidents, and other accidents. CO accept as the most common cause of poisoning cases in many countries and its prominent feature is being a colorless, odorless and nonirritant gas. In the period from 2007 until the end of 2011, the autopsy records of the ........ of Turkey were reviewed. Over a period of 5 years a total of 5782 autopsies were done of which 218 involved CO poisoning, constituting 3,8 % of total cases. Information regarding age, sex, month, year, and as well as various aspects were examined. Study data were encoded with computer and Statistical analysis was performed using SPSS for windows program. Of the cases 76 were (34,9%) female, 142 were (65,1%) male and male/female ratio was 1,9. Of the cases average age was 46.8, range between 1 and 90 years. 57,8% of deaths were in winter markedly. The highest carboxyhemoglobin saturation was 92% in the blood. Poisoning due to CO leaks from coal heaters is an important problem in our country and surrounding regions. The mining accidents should be reduced by increasing safety in the workplace. We must more expend efforts to educate the public and prevent CO poisoning. Key words: Carbon monoxide, poisoning, autopsy.